Persepsi Mahasiswa Mengenai Framing Keracunan Makanan Bergizi Gratis melalui Platform TikTok - Muhammad Aldi; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to explore students' perceptions of the social media framing phenomenon on TikTok regarding the poisoning case in the Free Nutritional Meal Program (MBG). The study used a descriptive qualitative method, collecting data through in-depth interviews with students from IPB University who actively use TikTok and were selected using purposive sampling based on the criteria of actively accessing TikTok content related to the MBG issue and being willing to participate as research informants. The results indicate two typologies of student perceptions in responding to content framing. The first group tends to accept the emotional narratives presented in TikTok content, contributing to the emergence of skeptical perceptions of the government. Meanwhile, the second group demonstrates a critical attitude by being able to identify the framing strategies used by content creators and cross-checking them with mainstream media before forming perceptions. The novelty of this study lies in identifying typologies of student perceptions in responding to the framing of TikTok content related to the Free Nutritional Meal Program issue and explaining the role of digital media literacy in mediating the process of forming these perceptions. This study concludes that dramatic framing in TikTok content is perceived as capable of evoking an emotional response from the audience, while students' digital media literacy levels act as information filters in the process of forming opinions on public policy issues.